Comparing the Effect of Inquiry-Based Multiple Intelligence Approach and Non-Inquiry Based Multiple Intelligence Approach on Achievement in Science - Samsudin, Mohd Ali; Subramaniam, Vasugi; Moses, Irekpita Simeon (Universitas Ahmad Dahlan, 2015)
The paper focused attention on comparing the effect of inquiry based multiple intelligence approach and noninquiry based multiple intelligence approach on achievement of pupils in some selected primary schools. Two primary schools were selected purposively with one intact class from each school. Each intact class of thirty (30) pupils were randomly assigned to the two groups used for the study. A total of sixty (60) pupils were used in the study. The two groups were assigned each to the inquiry based multiple intelligence approach group and the noninquiry based multiple intelligence approach group. The research design was a quasi-experimental design, involving a pretest and post-test in achievement of students. The reliability of the test instrument was established at 0.75 which was considered adequate. A pretest- was administered to the pupils .The pupils were taught science concepts based on the curriculum of the ministry of education for a period of eight (8) weeks using the inquirybased multiple intelligence approach and non- inquiry multiple intelligence approach for group A and B respectively after which the post-test- was administered. Findings using the statistical techniques of mean, median, standard deviation and one way analysis of covariant (ANCOVA) were used to proffer answers to the generated research questions and hypotheses revealed that there was significant difference between the achievement scores of pupils in science for the use of non- inquiry based multiple intelligence approach and noninquiry based multiple intelligence approach on. It was also statistically established that the effect of inquiry based multiple intelligence approach was on achievement is science was better. Conclusion and recommendations such as introducing and enhancing the use of inquiry based multiple intelligence approach in primary schools was made.